Cotton and Wool: Textile Economy in the Serakhs Oasis during the Late Sasanian Period, the Case of Spindle Whorls from Gurukly Depe (Turkmenistan) - Dominika Maja Kossowska-Janik (Ethnobiology Letters, 2016)
Gurukly Depe is an archaeological site located in the Serakhs oasis in southeast Turkmenistan, excavated since 2010 by the Polish-Turkmen archaeological mission directed by Professor Barbara Kaim from the University of Warsaw. Most investigated structures date to the Late Sasanian Period. At the site 102 spindle whorls were found. Based on their dimensions and weight I propose that most them were likely to have been used to spin cotton. This evidence provides another indication of cotton agriculture in Central Asia before the Muslim conquest.